Nonlinear interplay of Alfvén instabilities and energetic particles in tokamaks. (24th March 2017) - Biancalani, A; Bottino, A; Cole, M; Troia, C Di; Lauber, Ph; Mishchenko, A; Scott, B; Zonca, F
Abstract: The confinement of energetic particles (EPs) is crucial in the efficient heating of tokamak plasmas. Plasma instabilities such as Alfvén eigenmodes (AEs) can redistribute the EP population, making the plasma heating less effective and leading to additional loads on the walls. The nonlinear dynamics of toroidicity induced AEs (TAEs) is investigated by means of the global gyrokinetic particle-in-cell code ORB5, within the NEMORB project. The nonperturbative nonlinear interplay of TAEs and EPs due to the wave–particle nonlinearity is studied. In particular, we focus on the linear modification of the frequency, growth rate and radial structure of the TAE, caused by the nonlinear evolution of the EP distribution function. For the ITPA benchmark case, we find that the frequency increases when the growth rate decreases, and the mode shrinks radially. The theoretical interpretation is given in terms of a nonperturbative nonlinear evolution of the AE in relation to the Alfvén continuum.